Prospective randomized study to evaluate the feasibility and outcome of transmesocolic laparoscopic pyeloplasty and compare it with retrocolic laparoscopic pyeloplasty in pediatric and adolescent patients - Singh, Sanjeet Kumar (Medknow Publications & Media Pvt Ltd, 2014)
OBJECTIVE: This prospective randomized study was designed to evaluate the feasibility and outcome of transmesocolic laparoscopic pyeloplasty (TMP) and compare it with retrocolic laparoscopic pyeloplasty (RLP) in pediatric and adolescent patients. MATERIALS AND METHODS: Between September 2006 to May 2012, data of pediatric and adolescent patients undergoing laparoscopic pyeloplasty were recorded in a prospective manner. Data included age, pelvic volume, presence of stones, aberrant vessels, operative time, analgesics requirement and time to accept oral feeds and drain removal. Patients with left side pelviureteric junction obstruction with any size of pelvic volume, with or without renal stones and aberrant vessels were included in the study. Patients were assigned into two groups by simple randomization technique. A total of 38 TMP and 41 left sided RLP were performed. Median follow-up period for transmesocolic group was 12.5 months (9.5-62 months) and 14 months (8-66 months) for retro colic group. Outcome for this study was adequate drainage on renal scan, improvement in symptom and or resolution of hydronephrosis on ultrasound. Statistical analysis was performed using the Mann-Whitney test. RESULTS: The mean patient age was 8.73 years in RLP and 7.73 years in TMP. In RLP group the mean operative time was 75.84 min (time from port insertion to pyeloplasty) and 135.4 min (total operative time) while it was 44.82 min and 104.82 min respectively in TMP group. Compared with classic RLP, TMP cases showed a significant reduction in operative time. CONCLUSIONS: The transmesocolic approach for left sided pyeloplasty enables a shorter operative time even in the presence of large pelvis, aberrant vessel and stones without increasing morbidity in comparison to RLP approach.